Antiausteridad y protesta en el contexto de la crisis económica y política en España e Italia - Raffini, Luca; Penalva, Clemente; Alaminos, Antonio (SocietàMutamentoPolitica, 2015)
The crisis affecting European Union, and especially Mediterranean countries, is both an economic and a political crisis. In a broad sense, we can look at the crisis as the result of an internal crisis of the neoliberal model, exacerbating the perceived subordination of politics to the economy, and therefore the deficit of legitimacy and involvement that characterizes both European and national institutions. The decline in support for traditional political organizations and reduction of conventional political participation is accompanied by a process of reinvention of politics, which takes form in grass-root, non conventional participation. New political actors challenge economic and political institution and claim for a renewal of democracy and for a new relation between economy and politics. The article, after comparing steps and dimension of crisis, explores the characteristics of anti- austerity movements in Spain and in Italy, analyzing differences and similarities. Finally, we locate the movilization occurred in these two countries within the context of the global cycles of protest.